Stabilization of three-dimensional charge order in YBa2Cu3O6+x via epitaxial growth - M. Bluschke (Nature Portfolio, 2018)
In many cuprates the high temperature superconducting state competes with a charge ordered phase that has been difficult to investigate in detail. Here the authors show three-dimensional charge order can be stabilized in YBCO films and studied without using the high magnetic fields that are necessary in the bulk material.